Duel To The Death - Jance, Judith A. (New York : Touchstone, 2018)
"From New York Times bestselling author and "grand master of the game" (The Providence Journal) J.A. Jance, an electrifying new thriller featuring Ali Reynolds. After taking down the man responsible for his best friend's death, Stuart Ramey thinks the case is finally closed. That is, until Stu finds himself left with a multimillion dollar fortune in Bitcoin in a desperate bid by Frigg, a rogue A.I. program created by the killer, to keep itself from being fully deactivated. To sort out his situation and take Frigg down for good, Stu enlists the help of Ali Reynolds and the rest of his cyber security colleagues at High Noon Enterprises. But they are not the only ones who know about Frigg's existence. Graciella Miramar, an unassuming accountant to all appearances, is actually the right-hand woman to El Pescado, the leader of a dangerous drug cartel. She'll do anything to get her hands on that program. With Frigg's help, Graciella hopes to take over her father's criminal underworld and become wealthy beyond her wildest dreams. But Stu--and El Pescado and his henchmen--may not be so easily defeated. Written in J.A. Jance's classic "take-no-prisoners" style (Kirkus Reviews), in this thriller, Stu, Ali, and their team will come to realize that everything has its price"--
"The thirteenth book in New York Times bestselling author J.A. Jance's popular series featuring Ali Reynolds, a former Los Angeles news anchor turned amateur sleuth"--
Publishers Weekly
Library Journal Prepub Alert
Adult
Keywords: Reynolds, Ali (Fictitious character) -- Fiction; Women private investigators -- Fiction -- Arizona; Mystery fiction; Women detectives -- Fiction; Suspense fiction; Mystery fiction